Building the human values system of Vietnam by Resolution of the 13th Congress of the Communist Party of Vietnam - Nguyễn Thị Hiếu (Tạp chí Nghiên cứu Khoa học Công đoàn, 2024)
Building a Vietnamese human value system has a particularly great role and significance to promote the traditional values ​​of the nation and the strength of the Vietnamese people towards fulfilling the goal of "rich people, strong country and democracy, fair and civilized”. The view that the Resolution of the 13th Party Congress on building the Vietnamese human value system is realized and promoted will have a great effect, determining the achievements of the country in general and the comprehensive development of the people Vietnamese people in particular. In this article, the author focuses on studying aspects of building a Vietnamese human value system according to the Resolution of the 13th Congress of the Communist Party of Vietnam.